Pelatihan pencegahan dan penanggulangan bahaya kebakaran di fire station Bandar Udara Internasional Soekarno-Hatta - Kurniawan, Wahyu; Gunawan, Fandhy; Solihin, Solihin; Saputra, Surya Tri; Yusmana, Wawan; Kalbuana, Nawang; Supri, Supri (Penamas: Journal of Community Service, 2023)
The importance of awareness of fire risks in the community, especially at airports, encourages the need for effective prevention and countermeasures. Community service by lecturers of the D.III PKP Study Program through this training aims to provide knowledge and skills to the community of airport service users, especially workers in tenants, regarding how to prevent and overcome fires. Involving the Tri Darma Perguruan Tinggi concept, this training not only touches on aspects of fire prevention but also discusses fire phenomena, risk analysis, emergency response, and fire management. It is hoped that training participants will benefit them through increased knowledge and understanding that can increase awareness of fire risks so that the community around Soekarno-Hatta International Airport can be better prepared and trained in dealing with potential fire hazards.